Greenland Barnacle Geese in the British Isles - Ogilvie, M A; Boyd, H (Wildfowl, 1975)
Aerial censuses of the Greenland population of the Barnacle Goose Branta leucopsis wintering mostly on islands of the west and north coasts of Ireland and Scotland revealed an increase from 8,321 in December 1959 to 24,100 in March 1973. Simultaneously the proportion of the total wintering on the main haunt of Islay has risen from 34% to 62%. Changes in the use of sites and in the size of flocks are discussed in relation to the increasing importance of Islay. The conservation implications of this latter factor are reviewed.